Knowledge, attitudes, and practices regarding contraception amongst community pharmacy staff: a cross-sectional study in Nigeria - Adigwe, Obi Peter; Onavbavba, Godspower (Frontiers in Reproductive Health, 2025)
IntroductionLack of access to effective contraception methods can lead to an increased prevalence of unintended pregnancies, as well as possible deleterious health consequences. Community pharmacies represent the most accessible gateway for population medicines' and healthcare needs. Regarding contraceptives, they have also been identified as a platform for the provision of additional services, such as complementary counselling. This study aimed at assessing the knowledge, attitudes, and practices of community pharmacy staff towards contraception.MethodsA cross-sectional study was undertaken in the Federal Capital Territory, Nigeria. Data were collected from 315 community pharmacy staff using self-administered questionnaires. The participants' knowledge and attitude scores were categorised using Bloom's cut-off point. Analyses were undertaken using Statistical Package for Social Sciences. The data were analysed using frequency distribution, chi-square, and linear regression at a 5% level of significance.ResultsMale participants in the study (165/315, 52.4%) were slightly higher than the female respondents (150/315, 47.6%), and about two-thirds of the study cohort were pharmacists (200/315, 63.5%). The majority of the participants (183/315, 58.1%) had poor knowledge of contraceptive use. A quarter of them (81/315, 25.7%) reported moderate attitudes. Almost all the participants (279/298, 93.6%) indicated recommending contraceptives for married adults, and a significant proportion of them (136/292, 45.5%) were opposed to recommending contraceptives for unmarried adolescents. Study respondents' professional role was also identified as a significant influence on their knowledge of contraceptives and contraception (p < 0.001).ConclusionFindings from this study revealed poor knowledge and negative attitudes of community pharmacy staff towards contraception. Government and relevant stakeholders can build on these novel findings to reform pertinent contextual policies and practices. This can significantly improve access to contraceptives amongst the populace, and consequently reduce unintended pregnancies alongside possible health and societal implications.